2000
DOI: 10.1093/humupd/6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes in ovarian function

Abstract: It has become apparent that in the ovary, the immune system contributes to the regulation of gonadal function. Leukocytes present within the ovary may constitute potential in-situ modulators of ovarian function that act through local secretion of regulatory soluble factors. These factors include numerous cytokines that largely originate by the action of immune cells within the ovary. Actual rupture of the follicle during ovulation may be dependent on tissue remodelling that is characteristic of an acute inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(144 citation statements)
references
References 157 publications
8
122
0
3
Order By: Relevance
“…Увеличение содержания в фолли-кулярной жидкости IL-1ra, IL-7, IL-9, вероятно, отражает нарастание провоспалительного потен-циала с увеличением возраста больных. При этом с увеличением возраста выявлено повышение со-держания в фолликулярной жидкости PDGF BB [18] Известно, что PDGF является проангиоген-ным фактором, стимулирующим пролиферацию эндотелиальных клеток, перицитов и гладкомы-шечных клеток, обеспечивает стабилизацию со-судистого русла. Кроме этого, данный фактор влияет на миграцию и /или выживание этих кле-ток во время роста эндотелия.…”
Section: Discussionunclassified
“…Увеличение содержания в фолли-кулярной жидкости IL-1ra, IL-7, IL-9, вероятно, отражает нарастание провоспалительного потен-циала с увеличением возраста больных. При этом с увеличением возраста выявлено повышение со-держания в фолликулярной жидкости PDGF BB [18] Известно, что PDGF является проангиоген-ным фактором, стимулирующим пролиферацию эндотелиальных клеток, перицитов и гладкомы-шечных клеток, обеспечивает стабилизацию со-судистого русла. Кроме этого, данный фактор влияет на миграцию и /или выживание этих кле-ток во время роста эндотелия.…”
Section: Discussionunclassified
“…Ovarian IL-8 has been observed to be chemotactic for neutrophils and is also a potent angiogenic, pro-inflammatory, growthpromoting cytokine [23]. Bukulmez and Arici [16] have shown that local migration of neutrophils is hormonally regulated through local modulation of IL-8. Further studies investigating the correlation between HNP1-3 and other cytokines (IL-8 and TNF-α) known to have a more definitive role in ovulation may provide further information regarding the role of the defensins in folliculogenesis and ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are present in the medulla, theca, follicular fluid and corpus luteum [16]. The resident neutrophils in the ovary are thought to release TNF-!…”
Section: Introductionmentioning
confidence: 99%
“…Advocates of this so-called incessant ovulation hypothesis argue that repeated rupture of the ovarian surface during ovulation and subsequent repair by OSE proliferation may increase the frequency at which mutations arise. However, some have deemed this model too simplistic, since neither the effects of reproductive hormones nor acute inflammation is taken into account, both of which may be mutagenic (Bose, 2005;Bukulmez and Arici, 2000;Cramer and Welch, 1983;Fleming et al, 2006;Konishi, 2006;Mohle et al, 1985;Ness and Cottreau, 1999;.…”
Section: Disease Etiologymentioning
confidence: 99%